Occurrence and Quantification of Porcine Hemotrophic Mycoplasmas in Blood-Sucking Stomoxys calcitrans - Mareike Arendt; Katharina Hoelzle; Julia Stadler; Mathias Ritzmann; Julia Ade; Ludwig E. Hoelzle; Lukas Schwarz (Microorganisms, 2025)
Hemotrophic mycoplasmas (HMs) are cell wall-less, small and uncultivable pathogens, which can cause infections in pigs with no to severe clinical signs and can contribute to significant economic losses in the pig industry. In addition to the known mechanical transmission routes of HMs (e.g., via blood-contaminated instruments or lesions from ranking fights), transmission to pigs by arthropod vectors such as Stomoxys calcitrans is being discussed. To date, there is scant available data concerning the transmission of HMs by stable flies. The objective of this study is to gain more data concerning the occurrence of HMs in Stomoxys calcitrans. Therefore, quantitative real-time PCR was conducted on different stable fly samples (surface washings and whole flies). We found Mycoplasma (M.) suis in 5.2% of crushed flies and 4.2% of fly wash solutions, and M. parvum was detected in 5.2% of flies and 9.4% of fly wash solutions. ‘Candidatus (Ca.) M. haemosuis’ was not detected in any sample. The mean bacterial loads were 2.0 × 102 M. suis/fly, 9.3 × 102 M. suis/fly wash solution and, for M. parvum, 2.4 × 103 M. parvum/fly and 2.1 × 103 M. parvum/fly wash solution. This molecular occurrence of porcine HMs in blood-sucking flies and reasonable bacterial loads in the two- to three-digit range demonstrate that these flies serve as mechanical vectors in stables and are, therefore, of epidemiological importance.